Synthesis of Dispiro 1,3-Oxazepine4,7-Diones (Journal of the College of Basic Education, 2022)
Dispiro-1,3-oxazepine-4,7-diones can be synthesized by reaction of thiosemicarbazide with carbon disulphide in alcoholic anhydrous sodium carbonate gives 2-amino-5-mercapto-1,3,4-thiadiazole (I). Compound (II) were synthesized by the reaction of compound (I) with methyl iodide, this product hasbeen oxidized to sulphone derivatives. The Schiff's bases of the compounds(IVa,IVb) were synthesized by condensation of different aromatic aldehydes with sulphone derivatives, the Schiff' bases were cyclized with pyromelitic dianhydride to give dispiro-1,3-oxazepine -4,7-diones as shown in scheme[1]. The new compounds were characterized by physical properties and spectral data (FT-IR).